New science, drug regulation, and emergent public health issues: The work of FDA’s division of applied regulatory science - Chiu, Kimberly; Racz, Rebecca; Burkhart, Keith; Florian, Jeffry; Ford, Kevin; Iveth Garcia, M.; Geiger, Robert M.; Howard, Kristina E.; Hyland, Paula L.; Ismaiel, Omnia A.; Kruhlak, Naomi L.; Li, Zhihua; et al. (Frontiers in Medicine, 2023)
The U.S. Food and Drug Administration (FDA) Division of Applied Regulatory Science (DARS) moves new science into the drug review process and addresses emergent regulatory and public health questions for the Agency. By forming interdisciplinary teams, DARS conducts mission-critical research to provide answers to scientific questions and solutions to regulatory challenges. Staffed by experts across the translational research spectrum, DARS forms synergies by pulling together scientists and experts from diverse backgrounds to collaborate in tackling some of the most complex challenges facing FDA. This includes (but is not limited to) assessing the systemic absorption of sunscreens, evaluating whether certain drugs can convert to carcinogens in people, studying drug interactions with opioids, optimizing opioid antagonist dosing in community settings, removing barriers to biosimilar and generic drug development, and advancing therapeutic development for rare diseases. FDA tasks DARS with wide ranging issues that encompass regulatory science; DARS, in turn, helps the Agency solve these challenges. The impact of DARS research is felt by patients, the pharmaceutical industry, and fellow regulators. This article reviews applied research projects and initiatives led by DARS and conducts a deeper dive into select examples illustrating the impactful work of the Division.